PENGUATAN ETOS KERJA ISLAMI BERBASIS PHIWM DALAM MEMBANGUN KEIKHLASAN, LOYALITAS, DAN PROFESIONALITAS GURU SD MUHAMMADIYAH METRO - M. Samson Fajar; Dian Ayu Wita; Muhammad Nur (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This community empowerment program aimed to strengthen the Islamic work ethic of teachers and education staff at SD Muhammadiyah Metro through counseling based on Pedoman Hidup Islami Warga Muhammadiyah (PHIWM). The program addressed the need to integrate sincerity, loyalty, patience, and professionalism into everyday school culture. The method used was participatory counseling consisting of needs identification, preparation of PHIWM-based materials, interactive delivery, reflective discussion, and post-activity evaluation using a four-point instrument. The evaluation involved 29 valid respondents. The results show a very high overall score of 3.80 out of 4 or 94.94%. The highest dimension was orientation toward Allah’s pleasure at work (97.74%), while the relatively lowest dimension was progressive professionalism (90.41%). These findings indicate that spiritual commitment is strong, but innovation, discipline, competence development, and administrative punctuality require continuous strengthening.